SMEs AS DRIVERS OF ECONOMIC RECOVERY AND SUSTAINABILITY DURING COVID-19 AND BEYOND IN NIGERIA - NGUTSAV, AYILA; IJIRSHAR, VICTOR USHAHEMBA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
This study examined SMEs as drivers of economic recovery and sustainability in Nigeria during the COVID-19 pandemic and beyond. The study utilized primary data from a sample size of 387 SME owners across 13 states and FCT Abuja in Nigeria. The survey was carried out using online questionnaires through “Google Forms”. Descriptive statistics and paired t-test were used for data analysis. The findings showed that COVID-19 pandemic has drastically affected the level of employment and returns of SMEs in Nigeria negatively. Considering SMEs as critical engines of economic growth due to their potentials in creating jobs, boosting economic output, generating income, and reducing poverty, the study recommends that the Nigerian government should engage with the SMEs early, seek to better understand their challenges and how they might best mitigate the challenges that COVID-19 has caused. Some of the approaches are the granting of soft loans with a temporary moratorium of the loan or assisting the SMEs with grants, granting of SMEs payroll support programme, granting of relief programmes such as loan holiday packages for SMEs as measures mitigating against the effects caused by the COVID19 global pandemic. The study also recommends deliberate efforts towards improving innovativeness and managerial capabilities in SMEs that is focused on less finance and more innovation-based routes while creating support institutions to provide information on regulations, standards, taxation, customs duties, and marketing issues.